Comparative analysis of differentially expressed genes in breast cancer across Asian and European populations: insights into molecular pathways and biomarkers - Prabhu Meganathan; Sharvari Sawant; Shreshta Reddy (Exploration of Medicine)
Aim: Breast cancer (BC) is the most common malignancy among women and a leading cause of cancer-related mortality. Early detection and prediction are crucial for prognosis and targeted therapy selection. This study investigates differences in BC gene expression between European and Asian populations by analysing differentially expressed genes (DEGs) and identifying potential biomarkers for diagnosis and treatment. Methods: This study analyzed gene expression datasets from the NCBI Gene Expression Omnibus (GEO), including GSE15852 (Malaysia), GSE29044 (Saudi Arabia), GSE89116 (India), GSE61304 (Singapore), GSE29431 (Spain), GSE21422 (Germany), and GSE42568 (Ireland). DEGs were identified using GEO2R, with significance thresholds set at p < 0.05 and logFC > 2.0. Protein-protein interaction (PPI) networks were constructed using STRING and analyzed in Cytoscape, helping in identification of highly upregulated biomarker (HUB) genes. Functional enrichment was conducted using Enrichr-KG and GeneMANIA to explore pathway associations. Results: Two common HUB genes, cluster of differentiation 36 (CD36) and leptin (LEP), were identified across five datasets, suggesting their universal relevance in BC. Additionally, caveolin-1 (CAV1) and perilipin 1 (PLIN1) were significant in the Asian datasets, while CAV1, insulin-like growth factor 1 (IGF1), apolipoprotein B (APOB), and peroxisome proliferator-activated receptor gamma (PPARG) were HUB genes in European datasets. Functional pathway analysis revealed that these genes are primarily involved in cholesterol metabolism, adipocytokine signaling, AMP-activated protein kinase (AMPK) regulation, and fatty acid metabolism, highlighting their role in BC progression. Conclusions: CD36 and LEP are universal biomarkers with potential diagnostic and prognostic significance in BC. Region-specific HUB genes emphasize the need for precision medicine in treatment. Their role in cholesterol metabolism and adipocytokine signaling suggests potential therapeutic targets. CD36 and LEP could be used in liquid biopsy screening, and their metabolic function supports further investigation into CD36 inhibitors, LEP antagonists, and PPARG modulators. Future studies should focus on large-scale validation and multi-omics approaches for personalized BC management.